Oxford Dictionary of Geography - Mayhew S. Susan (Oxford paperback reference)
This invaluable dictionary provides comprehensive coverage in one volume of both human and physical geography. For this third edition, existing entries have been fully revised and updated, and 345 new new entries have been added, making this essential reference for all students of geography, whether at school or university. It is the most up-to-date dictionary of geography available, with over 6,000 clear and concise definitions. Authoritative entries encompass the range of the subject, including cartography, surveying, meteorology, climatology, ecology, population, industry, and development, and there is up-to-date treatment of topics such as plate tectonics, remote sensing, geographic information systems, and aerial differentiation. The Factfinder appendix with key economic and and population statistics for nearly 40 countries has also been brought fully up to date.